ANALISIS KETERAMPILAN MENGAJAR GURU TK YANG BERPENDIDIKAN S1 SE-KECAMATAN PAYUNG SEKAKI PEKANBARU - Sri Wahyu Ningsih; Zulkifli Zulkifli; Enda Puspitasari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstrak: The purpose of this study to determine the analysis of kindergarten teacher with bachelor’s of degree educated at Payung Sekaki district of Pekanbaru. Population and sample in this study were 22 people who had bachelor’s of degree educated at Payung Sekaki district of Pekanbaru. The data collection techniques that used was observation. Technique of data analysis was using a percentage formula. The results that obtained were teaching skills of kindergarten teacher at Payung Sekaki District of Pekanbaru overall was gain a percentage of 72.28% which is included in category of